2017
DOI: 10.1007/s12094-017-1657-7
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors reprogramming immunity in renal cell carcinoma: rethinking cancer immunotherapy

Abstract: The immune system regulates angiogenesis in cancer by way of both pro- and antiangiogenic activities. A bidirectional link between angiogenesis and the immune system has been clearly demonstrated. Most antiangiogenic molecules do not inhibit only VEGF signaling pathways but also other pathways which may affect immune system. Understanding of the role of these pathways in the regulation of immunosuppressive mechanisms by way of specific inhibitors is growing. Renal cell carcinoma (RCC) is an immunogenic tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 99 publications
(98 reference statements)
0
29
0
Order By: Relevance
“…Hypoxia‐inducible factor enhances the expression of proangiogenic factors such as VEGF and platelet‐derived growth factor. Although VEGF is an important inducer of angiogenesis, there is accumulating evidence that VEGF also has immunosuppressive effects . Therefore, ccRCC is an immunogenic tumor in which angiogenesis and immunosuppression work hand in hand, and its growth is associated with impaired tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia‐inducible factor enhances the expression of proangiogenic factors such as VEGF and platelet‐derived growth factor. Although VEGF is an important inducer of angiogenesis, there is accumulating evidence that VEGF also has immunosuppressive effects . Therefore, ccRCC is an immunogenic tumor in which angiogenesis and immunosuppression work hand in hand, and its growth is associated with impaired tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that both PD-1 and PD-L1 were pre- Note that the PD-1-positive TIIC score and PD-L1-positive TIIC score were associated with clinical effects of VEGF-TKI treatment, whereas the PD-L1-positive tumor score was not also has immunosuppressive effects. 22 Therefore, ccRCC is an immunogenic tumor in which angiogenesis and immunosuppression work hand in hand, and its growth is associated with impaired tumor immunity. Moreover, ccRCC is an immunological tumor that is often abundant in TIIC, 23 and most patients with metastatic RCC receive immunotherapy with interferon-α or interleukin-2 as the standard therapy before the introduction of molecular-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RTKIs targeting FGFR, in addition to their action on neoplastic cells, reduce the number of immunosuppressive MDSCs in the tumor and induce senescence of cancer-associated fibroblasts (CAFs) [65]. VEGFR1 inhibitors, in addition to their anti-angiogenic actions, can normalize tumor microvasculature and decrease the infiltration of MDSCS, Treg lymphocytes, and some populations of immunosuppressive tumor-associated macrophages (TAMs) [71,74].…”
Section: Impact Of the Immune Microenvironment On Receptor Tyrosine Kmentioning
confidence: 99%
“…The reason why SC hemorrhages so frequently is not clear, but we speculate that ETV6‐NTRK3 fusion gene has an important role. The product of this fusion gene induces angiogenesis through VEGF, and VEGF overexpression is known to induce tumor‐related cyst formation, peritumoral edema formation and hemorrhage . Furthermore, the papillary stromal components in SC were abundant in vessels, and the papillary formation is associated with angiogenesis in some tumors .…”
Section: Discussionmentioning
confidence: 99%
“…8 Tyrosine kinase is related to angiogenesis through vascular endothelial growth factor (VEGF). 9 Moreover, infantile fibrosarcoma and congenital mesoblastic nephroma with the ETV6-NTRK3 fusion product is usually macroscopically hemorrhagic. 10,11 Taken together, hemorrhage with hemosiderin deposition seems to be effective for separating SC from ACC, and we reviewed magnetic resonance imaging (MRI) findings, because MRI is the imaging modality of choice for evaluating hemorrhage and hemosiderin.…”
Section: Introductionmentioning
confidence: 99%